Green Function Formulism for Electromagnetic Wave Generated in Nanostructured Metamaterial of Finite Thickness: Isotropy and Anisotropy - Shunbo Li; Xiao Xiao; Bo Hou; Weijia Wen (International Journal of Optics)
A Green function formulism is developed to calculate the electromagnetic fields generated by sources embedded in nanostructured medium which could be represented by an effective electric permittivity tensor with finite thicknesses. The method begins with the decomposition of the generated mode into the eigenmodes in the medium, which have definite dispersions. To account the interface effect at boundaries, especially the mode conversion at the interface between anisotropic media, mode expansion method is combined into the theoretical framework. Thus, the electromagnetic wave in any given position can be gotten clearly. The formulism can provide conveniences of studying the novel properties of nanostructured metamaterials.